Neuronal defects an etiological factor in congenital pelviureteric junction obstruction?. Issue 1 (February 2018) - How, Guo Yuan; Chang, Kenneth Tou En; Jacobsen, Anette Sundfor; Yap, Te-Lu; Ong, Caroline Choo Phaik; Low, Yee; Allen, John Carson; Kuick, Chik Hong; Lim, Malcolm Zhun Leong; Laksmi, Narasimhan Kannan
Summary: Introduction: Congenital pelviureteric junction obstruction (PUJO) is one of the most frequent causes of neonatal hydronephrosis. Obstruction at the PUJ has potential severe adverse outcomes, such as renal damage. While pyeloplasty has been established as the definitive treatment, the exact pathophysiology of congenital PUJO remains unknown. Recent research has proposed neuronal innervation defects as an etiological factor in congenital PUJO. We aim to study the expression of various neuronal markers in PUJO specimens compared with controls, and evaluate whether severity of renal disease or dysfunction pre-operatively is related to expression of neuronal markers in resected PUJO specimens. Materials and methods: All consecutive patients who underwent dismembered pyeloplasty at KK Women's and Children's Hospital, Singapore, for intrinsic PUJO from 2008 to 2012 were included. Patients with other co-occurring renal pathologies were excluded. Controls were obtained from nephrectomy patients with Wilm's tumor or other benign renal conditions during the same period. Specimens were stained immunohistochemically with neuronal markers protein gene product 9.5 (PGP9.5), synaptophysin, and S-100, and with CD-117, a marker for interstitial cells of Cajal (Table). Levels of expression of the markers were assessed semiquantitatively (decreased, increased or no change) in comparison with controls by two independent observers. Pre-operative data of patients' renal anatomical (ultrasonography measurements of renal pelvis size) and functional parameters (differential renal function measured using MAG-3 renal scans) were obtained. Discussion: Thirty-eight PUJO specimens (38 renal units) and 20 controls were studied. Mean patient age at pyeloplasty was 25.3 months (2.9–167.6 months). Median pre-operative pelvic size was 25.0 mm (17.0–50.0 mm). Both PUJO specimens and controls showed great heterogeneity in distribution of innervation. All four immunohistochemical markers were not predictive of significant pre-operative renal pelvis dilation or pre-operative diminished renal function of the operated kidney. Conclusions: There exists marked variability in expression of neuronal markers synaptophysin, PGP9.5, and S-100, and CD-117 in PUJO specimens compared with controls. Our results show no clinical significance of the expression of neuronal markers in predicting degree of pre-operative renal pelvis dilation or differential renal function. The heterogeneity of expression of neuronal markers in PUJO specimens and controls in our population is at variance with prior studies. The etiology of PUJO is likely to be complex and multifactorial. Neuronal marker Function Synaptophysin - Most abundant integral membrane protein constituent of synaptic vesicles - Ubiquity in synapses allows for quantification of synapses - Function unknown PGP9.5 - Deubiquitinating enzyme in neurons and nerve fibers - Neuron-specific cytoplasmic marker CD-117 - Transmembrane tyrosine kinase growth factor receptor - Expressed in interstitial cells of Cajal, which generate and propagate electrical slow waves causing phasic contractions in gastrointestinal tract - Interstitial cells of Cajal present in renal pelvis and ureter S-100 - Function unknown - Specific marker for localizing cells of neural origin especially Schwann cells